Incidence of supraventricular tachycardia after inhaled short-acting beta agonist treatment in children. (3rd April 2021) - Woodward, Stephanie; Mundorff, Michael; Weng, Cindy; Gamboa, David G.; Johnson, Michael D.
Abstract: Introduction: Albuterol can trigger supraventricular tachycardia (SVT). The clinical characteristics, incidence, and risk factors of SVT after inhaled SABA treatment in children are currently unknown. Through review of regional care delivery, we will describe cases of SVT during asthma treatment in hospital-based settings, define the incidence of SVT in our population, and evaluate risk factors of SABA-induced SVT. Methods: We identified hospital-based care episodes of children 0-18 years old between 2006 and 2015 recorded in the Intermountain Healthcare EDW with either 1) diagnosis codes for both asthma and SVT or 2) both SABA and adenosine listed as billed medications. Controls were matched with cases by age and sex to determine risk factors for SVT after SABA using conditional logistic regression. Results: Of 93 care episodes meeting criteria, we found 7 cases of SVT after SABA treatment in 6 patients over 10 years. In our population, the incidence of SVT is 3.9 per 10, 000 episodes of SABA treatment, and 5.1 per 10, 000 children with asthma receiving hospital-based asthma care. Two episodes of SVT followed treatment with only levalbuterol, three after only albuterol, and two after both albuterol and levalbuterol treatment. Five cases of SVT were converted to sinus rhythm with adenosine, one converted with synchronized electrical cardioversion, and one resolved spontaneously. No cases of SVT led to death. No examined variables were associated with SABA-induced SVT. Conclusions: SVT is rare during hospital-based treatment for acute asthma using inhaled SABAs and has low morbidity and mortality.